Metodologia del diagnostico de la produccion de frijol - Ruíz de Londoño, Norha; Pachico, Douglas H. (United Nations Development Programme, 1985)
The objectives of the diagnosis of bean production are to (1) contribute criteria for the design and completion of on-farm trials of the new bean technology and (2) to take information to research centers that helps define bean research priorities. A summary is presented of the methodology suggested and practiced in national and international courses on on-farm research carried out by CIAT's bean program. (CIAT)